Contrast-Enhanced Computed Tomography in Intensive Care Unit Patients with Acute Clinical Deterioration: Impact of Hyperattenuating Adrenal Glands. Issue 1 (February 2017) - Boos, Johannes; Schek, Julia; Kröpil, Patric; Heusch, Philipp; Heinzler, Niklas; Antoch, Gerald; Lanzman, Rotem Shlomo
Purpose: The study sought to assess the frequency and prognostic value of hyperattenuating adrenal glands on contrast-enhanced computed tomography (CT) scans of surgical intensive care unit (ICU) patients with acute clinical deterioration. Methods: Eighty-eight consecutive ICU patients (63.2 ± 14.5 years of age) were included in this retrospective analysis. All patients underwent biphasic contrast-enhanced CT due to an acute clinical deterioration. Hyperattenuation of the adrenal glands was assessed subjectively and objectively. Subjective presence or absence of hyperattenuating adrenal glands was assessed by 2 blinded radiologists (J.B. and R.S.L.) in consensus. Hounsfield units (HU) were measured in the adrenal glands and in the inferior vena cava. Objective hyperattenuation was defined as HU (adrenal glands) > HU (inferior vena cava) with a 15-HU threshold. Death within 14 days following CT was set as endpoint and acquired from electronic patient data. Results: Thirty-eight patients (43.2%, Group Asubj ) exhibited hyperattenuation of the adrenal glands, whereas 50 patients (56.8%, Group Bsubj ) did not. Concerning the objective analysis, 31 patients (35.2%, Group Aobj ) exhibited hyperdense adrenal glands, whereas 53 patients (64.8%, Group Bobj ) did not. Overall 27 of 88 patients (30.6%) died within 14 days following the CT examination. Lethal outcome was significantly more frequent among patients in Group Asubj and Aobj (19 of 38 patients [50.0%] and 15 of 31 patients [48.4%]) as compared with patients in Group Bsubj (8 of 50 patients [16.0%]) and Group Bobj (12 of 57 patients [21.1%]; P < .05). Subjective and objective analysis correlated significantly ( P < .05). Conclusions: Hyperattenuation of adrenal glands on contrast-enhanced CT of ICU patients with acute clinical deterioration is associated with a high mortality and might serve as a prognostic marker for patients' outcome.